Very late stent thrombosis lacking findings of the typical causes on optical coherence tomography in a patient with SARS-CoV-2. Issue 3 (September 2022) - Shinkai, Wataru; Hashikata, Takehiro; Kameda, Ryo; Sato, Nobuhiro; Minami, Yoshiyasu; Ako, Junya
Abstract: A 50-year-old male was admitted to our hospital with sudden-onset chest pain. He was a current smoker with severe obesity and diabetes. He had a history of drug-eluting stent (DES) implantation in the left anterior descending artery (LAD) and had continuously taken clopidogrel. Eight days prior to admission, polymerase chain reaction testing confirmed that he was positive for severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). Emergent coronary angiography revealed total occlusion of previously implanted DES in LAD. Optical coherence tomography (OCT) images demonstrated the presence of large white thrombus within the well-expanded DES with homogenous neointima. There were no findings of malapposed strut, uncovered strut, intimal disruption, or neoatherosclerosis through the stented segment. Subsequent dilation using a drug-coated balloon successfully restored coronary flow in LAD. We experienced a case of very late stent thrombosis without findings of the typical causes on OCT images nor discontinuation of antiplatelet therapy in a patient with SARS-CoV-2. The present case suggests that SARS-CoV-2 infection may induce stent thrombosis irrespective of the presence of known causes and the status of antiplatelet therapy. Learning objectives: The underlying causes of very late stent thrombosis (VLST) include strut malapposition, neoatherosclerosis, uncovered struts and stent underexpansion in addition to inadequate discontinuation of antiplatelet therapy and/or systemic hyper coagulable state. The present case of VLST lacking those factors suggests the enhanced hyper thrombogenicity irrespective of the presence of known causes and the status of antiplatelet therapy in patients with severe acute respiratory syndrome coronavirus type 2.